The Role of Customer Engagement in Mediating the Influence of Brand Experience and Customer Satisfaction on the Customer Loyalty of Full-Service Airline in Indonesia - Roffianto Adi Nugroho; Ni Wayan Sri Suprapti (Journal of Business and Management Review, 2022)
The Corona Virus Disease-19 (COVID-19) pandemic, which is currently engulfing the entire world, has significantly reduced the number of air travel passengers worldwide. However, the decline in air travel passengers on domestic routes in Indonesia occurred in 2019, one year before the COVID-19 pandemic hit the aviation industry worldwide. The decline in passengers in 2019 can be taken as a signal of weakening demand in the aviation industry in Indonesia. This research was conducted on 233 respondents from the airline "X" as one of the full-service in Indonesia, which has also been affected by the decline in passengers since 2019. The strategy to increase customer retention during the COVID-19 pandemic and the post-pandemic period is an important thing to study, considering that the existing literature on airline customer loyalty has never been carried out under the conditions of the COVID-19 pandemic. Therefore, this study examines customer satisfaction, customer engagement, and brand experience as a combination of antecedent constructs of customer loyalty based on the perception of Indonesian passengers traveling with full-service airlines. The research shows that brand experience has no positive and significant effect on customer loyalty. Meanwhile, customer satisfaction and customer engagement positively and significantly impact customer loyalty. Furthermore, customer engagement can fully mediate the relationship between brand experience and customer loyalty of airline "X". In contrast, customer engagement can partially mediate the relationship between customer satisfaction and customer loyalty.